Is GnRH necessary at CIDR insertion using a 7-Day CIDR synchronization protocol for beef heifers? - D.R. Eborn; E.E. Blair; David M. Grieger (Kansas Agricultural Experiment Station Research Reports, 2011)
The EAZI-BREED CIDR is commonly used in estrous synchronization protocols for both beef heifers and cows. The label calls for insertion of a progesterone-impregnated controlled internal drug release (CIDR) for 7 consecutive days with an injection of prostaglandin F2αgiven a day before CIDR removal. Animals should display estrus 1 to 3 days after CIDR removal. Modifications to this protocol include administration of gonadotropin-releasing hormone (GnRH) at the time of CIDR insertion and administration of the prostaglandin injection at the time of CIDR removal on day 7. Use of GnRH in conjunction with a CIDR may improve estrous synchronization in beef cows and fertility at fixed-time insemination but may not be necessary when synchronizing beef heifers. Our objective was to compare heat response and fertility in heifers with or without GnRH administration at the time of CIDR insertion. Our hypothesis was that heifer fertility would be similar between treatments.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen' s Day; 2011; Beef; GnRH; CIDR; Synchronization rate